Introduction to the special issue on ethics, social responsibility and sustainability - Neves, J.; Simões, E.; Duarte, A. P. (Management Research: The Journal of the Iberoamerican Academy of Management, 2014)
In recent years, numerous scandals at financial institutions and companies, revealed an apparently previously unnoticed trend to frequent failures in ethical behavior within organizational activities. The analysis of those events has renewed scholars’ interest in the ethical problems in organizations, following two essential and complementary routes: one aims to understand how individuals make decisions on ethically dubious issues; another one is intended to grasp the antecedents and consequents of corporate social responsibility (CSR) and sustainability practices, namely, their influence on the ethicality of the organizational actors’ behaviors and decisions. Due to the relative consensus about its positive contribution to society, issues of CSR, ethics and sustainability are receiving increasing attention from scholars and practitioners, both in terms of application and research (Aguinis and Glavas, 2012; Carroll and Shabana, 2010; Duarte et al., 2010; Trevino and Nelson, 2004). However, particularly in the social sciences, no desideratum of scientific research is oblivious to the vicissitudes of the historical moment in which it arises. In the case of CSR, the times we live confront us with new problems that challenge previous assumptions about the effects of adoption of organizational guidance in this domain (Waddock, 2008). In fact, different, and often seemingly contradictory practices lead to question CSR underlying principles and rationale.